'We are the advocates for the babies' - understanding interactions between patients and health care providers during the prevention of mother-to-child transmission of HIV in South Africa: a qualitative study - Fiona Heerink; Anja Krumeich; Frans Feron; Ameena Goga (Taylor & Francis Group, 2019)
Background: HIV/AIDS has had a significant impact on maternal and child health in South Africa. It is thus of vital importance to implement interventions to prevent mother-to-child transmission of HIV (PMTCT) as early as possible during pregnancy. Negative interactions between patients and health care providers (HCPs) can be an important barrier to antenatal care, PMTCT use and PMTCT adherence. Research about respectful maternity care has focused more on the patient perspective. We therefore compared the patient and HCP perspectives and reflected on how interactions between HCPs and patients can be improved. Objective: To obtain insights into the attitudes of HCPs in the context of HIV and PMTCT-related care, by studying patient and HCP perceptions of their interactions, in a peri-urban hospital setting in Gauteng province, South Africa. Methods: A qualitative study was conducted in a public tertiary-level hospital. Fourteen semi-structured in-depth interviews were conducted with nurses and doctors in the antenatal clinic and postnatal ward. Thirty-one semi-structured in-depth interviews and two focus group discussions were conducted with HIV positive and negative women on the postnatal ward. Results: HCPs experienced a difficult work environment due to a high workload. This was combined with frustrations when they felt that patients did not take responsibility for their own or their child's health. They were motivated by the need to help the child. Patients experienced judging comments by HCPs especially towards younger, older and foreign women. They expressed fear to ask questions and self-blame, which in some cases delayed health care seeking. No discrimination or isolation of HIV infected patients was reported by patients and HCPs. Conclusion: We hypothesize that more humane working conditions for obstetric HCPs and a caring, personalised approach to patient management can improve patient-provider interactions and access to respectful care. These are critical to preventing mother-to-child transmission of HIV.